Host seeking in tsetse flies and functional genomics of hunger-driven behaviors in anopheles gambiae - (:unkn) unknown (My University, 2025)
Host seeking in tsetse flies (1) and functional genomics of hunger-driven behaviours in the mosquito Anopheles gambiae (2) 1. Host seeking in tsetse flies: The tsetse fly and the disease it transmits, African trypanosomiasis, cause a problem for human and agricultural systems that is unique in that both man and his livestock are affected. Maintenance of productive cattle in the presence of tsetse is very difficult, to the extent that tsetse flies largely remove cattle from farming activities in Africa. Studies on the host relations of savannah tsetse spp. have led to the development of reliable attractants that are used in combination with visual targets for control of G. morsitans morsitans and G. pallidipes. Riverine species of the palpalis group (such as the important vectors of disease G. palpalis gambiensis and G.fuscipes) and the forest species of the fusca group (such as G. brevipalpis) have not been investigated in detail. Our neurophysiolohical and behavioural studies on the latter tsetse fly spp. focuses on their responses to the rich variety of products regularly evacuated from the rumen of ungulates. This will permit us to establish chemosensory adaptations that are common to tsetse fly species. 2. Molecular regulation of Anopheles gambiae host-seeking and feeding: Anopheles gambiae Giles is the main vector of human malaria in sub-saharan Africa. Efforts for a better understanding of disease-vector insects have been enormously facilitated through the sequencing of the genome of this species. Our goal is to establish basic elements of the genetic control of host-seeking and biting behaviors in An. gambiae females – a matter of primary epidemiological importance. Host cue responses and feeding behaviors of female An. gambiae are subject to regulation that depends on the nutritional and hydration state of the insect. This regulation involves a network of signaling pathways such as the widely conserved insulin signaling pathway. This research focuses on the expression level of several genes in the regulation of host-seeking and feeding behaviors. Gene expression levels and protein localization (established by immunocytochemistry) are evaluated in several organs of An. gambiae and show differential responses depending on the physiological state of the mosquito. This work will provide an insight into the regulation of disease-transmitting behaviors in An. gambiae.
Keywords: tsetse flies; glossina spp.; host seeking; mosquito; anopheles gambiae; functional genomics